Agriculture commercialisation, household dietary diversity and nutrition in Tanzania. (November 2022) - Julius Chegere, Martin; Sebastian Kauky, Monica
Highlights: Agriculture commercialization can promote household income, and nutrition security. Linkage between agriculture commercialization, dietary diversity and nutrition is crucial. Agriculture commercialisation is mainly determined by area of land cultivated. Agriculture commercialisation has significant effect on dietary diversity for lower income group but not for the whole sample. Agriculture commercialisation and dietary diversity have insignificant effect on child nutrition. Policies to promote nutrition should be holistic. Abstract: Availability and accessibility of proper amount and variety of foods are important determinants of household nutritional status. Agriculture commercialisation can be a useful means of promoting efficiency in agriculture, increasing agricultural household income and consequently, improving household food and nutrition security. Using the first three waves of Tanzania National Panel Survey data, this paper employs panel data models to analyse the linkages between agriculture commercialisation, dietary diversity, and nutrition status in Tanzania. It contributes to the literature by assessing those linkages across different income groups. The study finds that agriculture commercialisation has a significant effect on dietary diversity for the lower-income group; but not for the whole sample. Education levels of the head of household and of the highly educated female member, overall income levels and area of land cultivated have positive and significant effects on dietary diversity; whereas age of the head has negative and significant effect. It also finds that agriculture commercialisation and household dietary diversity both have an insignificant effect on child stunting, wasting, and underweight even for the lower-income group. Findings imply that policies favouring commercialisation and dietary diversification may not necessarily translate to improving child nutrition. Addressing nutrition challenges requires all-encompassing strategies.